Bread preparation by partial replacement of wheat by germinated sorghum - Sharanagat, Vijay Singh (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2023)
Published literature shows significant impact of sorghum type and flour on end-product quality, while demonstrating paucity in the studied varieties with respect to processing aspects (such as bread making) despite of enormous accessions available worldwide. Limited studies have reported usage of germinated flour for the above said purpose. The present study thus aimed at mitigating these gaps by utilizing results of sorghum (HJ-513) germination (Day 1-5) and flour derived from optimized condition (Day 3 as identified by partial least square analysis) to develop a composite functional bread (partial replacement of wheat). The germination process enhanced the total phenolics compounds (TPC, till day 3), water (14.01%) and oil absorption capacity (25.97%) while reducing the bulk density (760.99-644.69 kg/m3). This demonstrated increased potential of sorghum flour for development of bakery and confectionery products. The process also affected the pasting properties, total flavonoids compounds (TFC) and DPPH (2, 2-diphenyl-1-picrylhydrazyl) significantly (p < 0.05). The bread developed from partial replacement (10% and 20%) of refined wheat flour by sorghum was hard and darker than the control wheat bread. The bread developed at 20% was more dense and porous than the bread developed with 10% replacement. Specific volume of bread at 10% replacement was found higher than at 20% replacement. The study reports effective utilization of germinated sorghum flour for development of composite-functional bread without incorporation of any other additives/improvers. Future research however is warranted in the field to further increase the replacement of wheat flour by germinated sorghum flour to develop gluten free bread